2015
DOI: 10.1590/1678-4162-8196
|View full text |Cite
|
Sign up to set email alerts
|

Diagnóstico do complexo teníase-cisticercose bovina em São João Evangelista, Minas Gerais, Brasil

Abstract: RESUMOCom o objetivo de diagnosticar a situação do complexo teníase-cisticercose bovina em Minas Gerais, Brasil, foi selecionado o município de São João Evangelista, onde foram coletadas amostras de sangue de 339 bovinos em 15 propriedades rurais, sorteadas aleatoriamente. Em cada propriedade, foi aplicado um questionário socioeconômico para a análise de fatores que favorecem a manutenção do complexo teníase-cisticercose bovina. Foi realizado também o diagnóstico de teníase humana por meio de exame coproparasi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0
3

Year Published

2017
2017
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 9 publications
0
2
0
3
Order By: Relevance
“…Studies addressing the prevalence of bovine cysticercosis in the states of Rio de Janeiro, Paraná, Bahia, Espírito Santo, and Minas Gerais reported rates of 3.83%, 3.97%, 1.95%, 1.74%, and 4.1%, respectively (Pereira et al 2006, Souza et al 2007, Santos et al 2008, Cipriano et al 2015, Garro et al 2015, indicating that cysticercosis is an endemic disease in Brazil. Researchers believe that the prevalence of bovine cysticercosis is underestimated in Brazil, as it is mainly based on records of post-mortem inspection -a method that is often inefficient especially in the detection of mild infections (Santos et al 2008, Bavia et al 2012, in addition to unsupervised slaughter, in which lesions are not reported to the inspection service (Pereira et al 2006, Santos & Barros 2009.…”
Section: Discussionmentioning
confidence: 99%
“…Studies addressing the prevalence of bovine cysticercosis in the states of Rio de Janeiro, Paraná, Bahia, Espírito Santo, and Minas Gerais reported rates of 3.83%, 3.97%, 1.95%, 1.74%, and 4.1%, respectively (Pereira et al 2006, Souza et al 2007, Santos et al 2008, Cipriano et al 2015, Garro et al 2015, indicating that cysticercosis is an endemic disease in Brazil. Researchers believe that the prevalence of bovine cysticercosis is underestimated in Brazil, as it is mainly based on records of post-mortem inspection -a method that is often inefficient especially in the detection of mild infections (Santos et al 2008, Bavia et al 2012, in addition to unsupervised slaughter, in which lesions are not reported to the inspection service (Pereira et al 2006, Santos & Barros 2009.…”
Section: Discussionmentioning
confidence: 99%
“…Data on bovine cysticercosis prevalence using serological methods as diagnostic tests in Brazil are scarce and limited to local surveys. Seropositivities rates at animal level have been referred to range from 0.4% to 4.1% in surveys conducted in the state of Minas Gerais (IASBIK et al, 2010;ACEVEDO et al 2012;SANTOS et al, 2013;FELIPPE et al, 2014;GARRO et al, 2015). It seems that the herd-level prevalence could be even higher in Paraíba, once for this study only cows aged ≥ 24 months were used.…”
Section: Resultsmentioning
confidence: 99%
“…no Brasil varia de 0,21 a 2,83%. A menor prevalência de teníase quando comparada a outras parasitoses intestinais também foi observada por outros autores e pode ser explicada pela baixa sensibilidade do método HPJ (Garro et al 2015). Esta técnica é empregada rotineiramente nos laboratórios de análises clínicas devido à facilidade de execução e baixo custo, porém, devido à grande quantidade de detritos fecais no sedimento, o diagnóstico pode se tornar difícil, principalmente em amostras com baixa carga parasitária (Cantos et al 2011).…”
Section: Resultsunclassified